The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+3 votes
179 views
Let X∈{0,1} and Y∈{0,1} be two random variables if P(X=0) =p and P(Y=0)=q then P(X+Y>=1) is equal to

1)pq+(1-p)(1-q)

2)pq

3)p(1-q)

4)1-pq
asked in Probability by Veteran (33.2k points) | 179 views

1 Answer

+5 votes
Best answer
 X∈{0,1}  Y∈{0,1}
i.e. for P(X+Y>=1) value of X and Y can be {(0,1),(1,0),(1,1)} 
So we can say , P(X+Y>=1) = 1-P(X+Y<1)
                                                  = 1- P(X=0,Y=0)
                                                 =1-  {P(X=0).P(Y=0)}
                                                 =1-pq
                                                                                   

 

answered by Veteran (70k points)
selected by


Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

28,982 questions
36,818 answers
91,195 comments
34,706 users